The Effect Of Warm Compresses Of Ginger Decoction And Exercises Range Of Mation (Rom) To Decreased Joint Pain For The Elderly At Posyandu Tengger Lor Kediri Village - Auliyatin Nimah Al Busyari; Linga Kusuma Wardani (Journal of Health Science Community, 2023)
At the elderly level, many experience a decrease in biological function, one of which is joint pain in the elderly so that it will interfere with limited movement in the joints. To maintain health, it is necessary to have good efforts in the nature of treatment, pharmacological and non-pharmacological treatment. Nonpharmacological treatment such as warm compresses of ginger decoction and range of mation exercises (ROM). This research design uses Quasi Experiment With Rendom Two Groups Design Approach, Posttest Only. Samples were taken using Simple Random Sampling from January 16 to January 20, 2023. The sample was 41 respondents and grouped into two groups, namely 20 respondents of the warm compress group of ginger decoction and 21 respondents of the range of mation (ROM) exercise group. This research instrument uses observation sheets.The results of the Mann-Whitney test are known that the average value of pain in respondents given warm compress therapy of ginger decoction is 10.50 and the average value of pain in respondents given range of mation (ROM) exercise therapy is 10.00. As for the P value = 0.006 < 0.05 which means there is a significant difference between warm compress therapy of ginger decoction and range of mation (ROM) exercises, where the warm compress technique of ginger decoction is more effective in reducing joint pain in the. Doing warm compresses of ginger decoction regularly can reduce pain in the joints and provide a feeling of comfort in the body.